PELATIHAN IMPLEMENTASI MANAJEMEN MUTU DI RUMAH SAKIT UMUM SEMBIRING DELI TUA - Sri Sudewi Pratiwi Sitio; Saiful Batubara; Efrata s; Bahtera Bindavid Purba (INSTITUT KESEHATAN DELI HUSADA, 2021)
Hospital quality management is aimed at improving the quality of health services and protecting patients and increasing satisfaction with the use of services in hospitals. In addition, quality management is also related to hospital accreditation which is part of the national hospital quality assurance system. 7 quality management principles developed in ISO 9001: 2015 which include: (1) Customer Focus; (2) Leadership; (3) Engagement of People Process; (4) Approach; (5) Improvements; (6) Evidence-Based Decision Making & (7) Relationship Management. It needs to be implemented and integrated into the hospital's internal quality assurance system as a form of strengthening the standards and criteria that are developed sustainably in the hospital.